Leveraging credit ratings through impression management: An exploratory study of German small and medium-sized family firms - Ludwig Marrenbach (Junior Management Science (JUMS), 2024)
In an era marked by multi-crisis environments, the significance of corporate finance and credit ratings amplifies, especially for German small- and medium-sized family firms, often constrained in accessing capital markets. This thesis investigates how family firms employ impression management strategies within qualitative credit ratings to enhance their creditworthiness. Through exploratory qualitative research involving 17 interviews with German family firms and banks, primarily financing the Mittelstand, three key dimensions of impression management emerge: family-specific, business-specific, and relationshipspecific tactics. Family-specific factors, including values and generational succession, significantly influence qualitative credit rating scores. Moreover, the interplay between firms and banks, orchestrated by the owning family, shapes effective impression management strategies. This research underscores the role of family involvement in shaping qualitative credit ratings, emphasizing the interrelations among family, business, and banking dynamics. The discussion highlights the relevance and adaptability of these impression management dimensions, contributing to a deeper understanding of qualitative credit rating processes within the context of family firms.
Keywords: 330; credit rating; family firm; impression management; leveraging credit ratings; qualitative rating factors